Bio-fortification of calcium, zinc and iron improves yield and quality of forage sorghum (Sorghum bicolor L.) - Asif, Muhammad; Abbas, Basharat; Aziz, Ahsan; Adnan, Muhammad; Safdar, Muhammad Ehsan; Ali, Amjed; Raza, Ali; Hanif, Muhammad Shakeel (Journal of Pure and Applied Agriculture, 2023)
Sorghum (Sorghum bicolor L.) is an important summer fodder crop. It is a quick growing grass which requires low inputs. Deficiency of major micronutrients {calcium (Ca), zinc (Zn) and iron (Fe)} is common in sorghum which creates some health problems in livestock. Therefore, the study was conducted during summer 2018 at Agronomic Research Farm, College of Agriculture, University of Sargodha Pakistan to evaluate the impact of calcium (Ca), zinc (Zn) and iron (Fe) bio-fortification on yield and quality of forage sorghum under field conditions. Experiment was laid out in randomized complete block design (RCBD) with 4 replications, t